ChemInform Abstract: An Active, General, and Long‐Lived Palladium Catalyst for Cross‐Couplings of Deactivated (Hetero)aryl Chlorides and Bromides with Arylboronic Acids. Issue 18 (17th April 2014) - Hoshi, Takashi; Honma, Tomonobu; Mori, Ayako; Konishi, Maki; Sato, Tsutomu; Hagiwara, Hisahiro; Suzuki, Toshio
Abstract A ligand for the Suzuki‐Miyaura coupling reaction of a broad range of aryl halides and aryl boronic acids is presented.